Landscape Connectivity For Wildlife and Water: The State of the Literature - Ruth DeFries; Satvik Parashar; Amrita Neelakantan; Benjamin Clark; Jagdish Krishnaswamy (Current Landscape Ecology Reports, 2023)
Purpose of Review The science of landscape connectivity is widely applied to identify corridors for wildlife movement through unprotected areas. Where corridors coincide with forested or vegetated headwater catchments, they can contribute to blue water security for downstream users and recycle precipitation through green water flux to the larger region. This review examines the extent to which hydrology is recognized within studies on wildlife corridors. We illustrate the synergy between wildlife corridors and water security in the Central Indian Highlands, a globally important region for tiger ( Panthera tigris ) conservation and the water tower for five major rivers. Recent Findings We find that a growing but still minor component of the literature on landscape connectivity addresses hydrology. Out of 127 publications on landscape connectivity that address both hydrology and wildlife, 50% were published after 2015 and hydrology-related words appear more frequently in abstracts over time (27% in 1993–2003 and 45% in 2014–2023 of most frequently used words) The case study illustrates potential synergies for water security and conservation, with areas for wildlife connectivity twice as rugged, three times more forested, and about 1.8 times denser with small streams than other areas in the landscape. About half of the area identified for landscape connectivity overlaps with catchment areas for five major dams. Summary Freshwater resources and water security are vital in human-dominated landscapes such as central India. A holistic view of landscape connectivity beyond wildlife provides practitioners with additional rationale for conserving these areas to maintain water resources that are directly relevant to people living in the landscape.